Evaluation of a clinical attachment in Primary Health Care as a component of undergraduate medical education. - Mariolis, Anargiros; Mihas, Constantinos; Alevizos, Alevizos; Papathanasiou, Marek; Mariolis-Sapsakos, Theodoros; Marayiannis, Konstantinos; Koutsilieris, Michael (Med Teach, 2008)
INTRODUCTION: It seems that there is a trend in undergraduate medical education towards including clinical attachments in primary health care (PHC) worldwide. The benefits of such initiatives are already well described. The aim of this study was to evaluate the effect of a clinical attachment in undergraduate medical students in a European country with an odd medical educational system that essentially lacks any kind of academic PHC departments. METHODS: The study was undertaken during 2005-2007. A non-mandatory 1-week clinical attachment in PHC/general practice was organized in an urban PHC unit by general practitioners with educational experience in collaboration with the Department of Physiology of the local medical school. The participants were a prospective cohort of medical students in the 2nd year of undergraduate studies. All participating students sat a pre-defined clinical exam which consisted of multiple choice questions, mini case papers and an objective-structured clinical examination before and after the attachment. In addition, the students rated the whole process. RESULTS: The response ratio was 77.06%. The mean score on objective structured clinical examination of participants increased from 30.70/100 to 62.28/100 (p < 0.001). The students' impression of the study was rather positive (4.39/5). DISCUSSION: The educational intervention of including a clinical attachment in an undergraduate curriculum seems to have encouraging results, considering the peculiarity of inexistence of academic departments of PHC or General Practice in the national medical schools and the inexperience of students regarding similar concepts.
Keywords: Career Choice; Clinical Competence; Curriculum; Education, Medical, Undergraduate; Educational Measurement; Europe; Female; Humans; Male; Primary Health Care; Prospective Studies; Surveys and Questionnaires; Young Adult